Principles of customer relationship management - Baran, Roger J. (Thomson/South-Western, 2008)
The textbook is lively and will hold students' interest with its unusual and interesting vignettes from the gaming, hotel, banking, airline, charge-card, supermarket, retailing, and package goods industries. This book acquaints students with the various approaches and applications but does not dwell on the underlying statistics. A second approach focuses on the strategic side of customer relationship management. The text provides students with an understanding of Customer Relationship Management and its application in the business